2005
DOI: 10.1182/blood-2004-11-4422
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin, a key component of the hematopoietic stem cell niche and regulator of primitive hematopoietic progenitor cells

Abstract: Although recent data suggests that osteoblasts play a key role within the hematopoietic stem cell (HSC) niche, the mechanisms underpinning this remain to be fully defined. The studies described herein examine the role in hematopoiesis of Osteopontin (Opn), a multidomain, phosphorylated glycoprotein, synthesized by osteoblasts, with well-described roles in cell adhesion, inflammatory responses, angiogenesis, and tumor metastasis. We demonstrate a previously unrecognized IntroductionHematopoietic stem cell (HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
549
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 683 publications
(584 citation statements)
references
References 53 publications
31
549
1
3
Order By: Relevance
“…Nothing has been reported so for with respect to a likely connection of these cytokines and OPN in BM and aging, though a recent study reported increased IP‐10 serum levels in elderly patients (de Bonfante et al , 2015). As implied by previous studies (Nilsson et al , 2005; Stier et al , 2005; Grassinger et al , 2009), our results further confirm that OPN cleaved by thrombin is biologically active. OPN is a secreted glycoprotein able to bind HSCs through, among others, interactions with CD44 and α 9 β 1 /α 4 β 1 integrins (Stier et al , 2005; Grassinger et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nothing has been reported so for with respect to a likely connection of these cytokines and OPN in BM and aging, though a recent study reported increased IP‐10 serum levels in elderly patients (de Bonfante et al , 2015). As implied by previous studies (Nilsson et al , 2005; Stier et al , 2005; Grassinger et al , 2009), our results further confirm that OPN cleaved by thrombin is biologically active. OPN is a secreted glycoprotein able to bind HSCs through, among others, interactions with CD44 and α 9 β 1 /α 4 β 1 integrins (Stier et al , 2005; Grassinger et al , 2009).…”
Section: Discussionsupporting
confidence: 92%
“…In both Y→OPN KO and Y→O transplants, a decrease in the overall donor‐derived cell engraftment in PB was observed compared to Y→Y (Fig 3G). Y→OPN KO mice showed an aging‐like increase in the frequency of HSCs in BM that was indistinguishable from the frequency in Y→O, but very distinct from Y→Y controls (Fig 3H) as also already described for early hematopoietic progenitor cells (LSK) cells in OPN −/− animals (Nilsson et al , 2005). Y→O animals presented with an increase in the frequency of myeloid cells over lymphoid T cells, while B‐cell frequencies were not affected (Fig 3I, see also Fig 1).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations